Internalisasi Nilai Moderasi dalam Proses Pembelajaran Pendidikan Agama Islam di Perguruan Tinggi Umum - Raharjo, Sudi; Miftahuddin; Lopo, Ferdinan Leonadus (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The internalization of moderation values in the teaching of Islamic Religious Education (PAI) at public universities is a strategic effort to cultivate young generations with an inclusive, tolerant, and adaptive Islamic perspective in response to global dynamics. This study aims to analyze the approaches used to internalize moderation values in PAI learning processes, focusing on how these values can be effectively integrated into curricula and learning activities. The research employs a qualitative method with a literature review and library research approach, referencing various sources such as scientific journals, books, policy documents, and previous research reports. The findings reveal that the internalization of moderation values in PAI teaching can be achieved through an integrative approach, where values such as tolerance, justice, and harmony are incorporated into teaching materials, learning methods, and assessment processes. Additionally, the use of discussion methods, case studies, and project-based learning on moderation values has proven effective in fostering understanding and moderate attitudes among students. However, challenges include resistance from some groups who do not fully comprehend the importance of moderation, insufficient training for lecturers, and limited literature supporting the application of moderation values in local contexts. This study recommends that public universities enhance lecturer training, develop moderation-based teaching modules, and encourage collaboration with various stakeholders to support the successful internalization of moderation values in PAI teaching. With this approach, universities are expected to produce graduates who not only possess academic competence but also contribute to building a harmonious and tolerant society.